Penerapan Prinsip Kehati-Hatian Dan Kepastian Hukum Dalam Penerbitan Sertifikat Hak Atas Tanah Oleh Kantor Pertanahan Kabupaten Nagekeo - Hendrikus Krisanto Mario Djawa Tay; Agustinus Hedewata; Yossie M. Y. Jacob (Universitas Sains dan Teknologi Komputer, 2024)
Land in the juridical sense is the surface of the earth, land rights are rights to a certain portion of the earth's surface, which is limited, has two dimensions with length and width. No human being or any group of people can be separated from land. Land can be used for development, both in infrastructure such as roads, irrigation, telecommunications and in the fields of agriculture, animal husbandry, mining, housing so that currently land has very high economic value. This will of course trigger land disputes. One of the factors that causes land disputes is the large number of lands owned by residents who do not yet have land certificates, and also in the process of issuing land certificates, the principle of caution in examining juridical and technical data is not implemented properly. Based on the background above, the problem formulation is put forward as follows: (1) Has the Nagekeo Regency Land Office in issuing land title certificates paid attention to the precautionary principle? (2) Does the land title certificate issued provide legal certainty and act as strong evidence? This research was carried out at the Nagekeo District Land Office. This research is empirical legal research, which is carried out by looking at the realities that exist in field practice. Based on the results of the research that has been carried out, it was found that: (1) To find out the application of the precautionary principle in issuing land title certificates, it can be seen from the land services provided by the Nagekeo Regency Land Office, which refers to the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 1 of 2010 concerning Service Standards and Land Regulation. The procedure for issuing activity certificates includes checking juridical data and checking technical data. (2) The land title certificate issued guarantees legal certainty and is strong evidence but is not the only evidence so that the certificate issued can still be challenged.